The Idea of Welfare State vs the Idea of Sustainable Development. The Case for United Kingdom - Omelan, Grzegorz (Studia Krytyczne/Critical Studies, 2019)
Within the last decades Great Britain has developed a specific model of welfare state. The “from-cradle-to-grave” model is close to the hearts of Labour Party’s politicians and supporters, on the other hand Conservative Party’s governments have been trying to limit welfare state’s reach since 1979. Cameron’s cabinet introduced a significant reform of the system, depriving many Brits of their benefits and lowering the number of people eligible to claim one. It is advisable to consider if these policies go hand in hand with the idea of sustainable development in the socio-economic context.